Описание экспериментальной установки для исследования гидростатодинамического подпятника с карманами Рэлея - Сорокина, Татьяна Николаевна (НТУ "ХПИ", 2015)
Рассмотрено описание экспериментальной установки для исследования гидростатодинамического подпятника с карманами Рэлея на различных режимах эксплуатации. В работе приведены основные компоненты и системы этой установки, конструкция и устройство модернизированной экспериментальной головки, расположение и особенности нагрузочного устройства, состав и конструкция опытного образца гидростатодинамического подпятника с выравнивающим устройством, типы и назначение установленных датчиков и приборов регистрации, состав и описание автоматизированного комплекса регистрации параметров и приборов контроля.

This article is devoted to the experimental facility description for hybrid Reyleigh step bearing.There is considered the experimental facility description for hybrid Reyleigh step bearing at the different regimes of exploitation. There is determined the necessity of bearing efficiency checking and gives the opportunity to analyze the adequate theoretical calculation researches on the basis of chosen improved method of the hybrid Reyleigh step bearing static characteristics calculation in the turbulent regime. The experimental facility for hybrid Reyleigh step bearing was modernize with a purpose to check the static characteristics at the different range of load, of rotor speed rotations and oil supply pressure to the oil system. Its systems and components appointment was studied in the paper. The modernized experimental facility allows testing the hybrid bearing in start and stopping regimes. Sensors and parameters registration automated complex were permitted to continuously fix the oil temperature parameters at the area of oil supply, in the pocket and in the bearing working surface and to control the oil stratum size depending on enclosed load at the different regimes. Bearing experimental sample was installed to the cardan type compensating device and allows compensating natural side shaft whipping.
Experimental facility description for hybrid Reyleigh step bearing
Keywords: экспериментальная головка; упорный подшипник скольжения; УПС; турбулентное течение смазки; experimental head